ANALYSIS OF VIOLIN PLAYING TECHNIQUES œCONCERTO IN G MINOR 3RD MOVEMENT BY ANTONIO VIVALDI - Senthod Setia Budi (Repertoar, 2021)
This study aims to describe the playing techniques and violin runners in Antonio Vivaldi's Concerto in g Minor 3rd Movement. This study used qualitative research methods. Data obtained in research through observation, interviews and documentation. The data analysis technique used was data reduction, data presentation and data conclusion. And there is a data validity test using triangulation techniques. The results showed that the playing techniques of Antonio Vivaldi's Concerto in g Minor 3rd Movement consisted of legato, ligatura, staccato, detache and accent. The ornaments contained in it, namely appogiatura, trill and fermata. While the positions of the fingers used in this repertoire are positions 1, 2, 3 and 4.